A Molecular Staple: D-Loops in the I Domain of Bacteriophage P22 Coat Protein Make Important Intercapsomer Contacts Required for Procapsid Assembly - D'Lima, Nadia G. (J Virol, 2015)
Bacteriophage P22, a double-stranded DNA (dsDNA) virus, has a nonconserved 124-amino-acid accessory domain inserted into its coat protein, which has the canonical HK97 protein fold. This I domain is involved in virus capsid size determination and stability, as well as protein folding. The nuclear magnetic resonance (NMR) solution structure of the I domain revealed the presence of a D-loop, which was hypothesized to make important intersubunit contacts between coat proteins in adjacent capsomers. Here we show that amino acid substitutions of residues near the tip of the D-loop result in aberrant assembly products, including tubes and broken particles, highlighting the significance of the D-loops in proper procapsid assembly. Using disulfide cross-linking, we showed that the tips of the D-loops are positioned directly across from each other both in the procapsid and the mature virion, suggesting their importance in both states. Our results indicate that D-loop interactions act as “molecular staples” at the icosahedral 2-fold symmetry axis and significantly contribute to stabilizing the P22 capsid for DNA packaging. IMPORTANCE Many dsDNA viruses have morphogenic pathways utilizing an intermediate capsid, known as a procapsid. These procapsids are assembled from a coat protein having the HK97 fold in a reaction driven by scaffolding proteins or delta domains. Maturation of the capsid occurs during DNA packaging. Bacteriophage HK97 uniquely stabilizes its capsid during maturation by intercapsomer cross-linking, but most virus capsids are stabilized by alternate means. Here we show that the I domain that is inserted into the coat protein of bacteriophage P22 is important in the process of proper procapsid assembly. Specifically, the I domain allows for stabilizing interactions across the capsid 2-fold axis of symmetry via a D-loop. When amino acid residues at the tip of the D-loop are mutated, aberrant assembly products, including tubes, are formed instead of procapsids, consequently phage production is affected, indicating the importance of stabilizing interactions during the assembly and maturation reactions.